Advocating for your department during a school merger: The chair perspective - Mark Urtel; Amanda Cecil (Academic Chairpersons Conference Proceedings, 2019)
This presentation will foster discussion and reflection on best practices in advocating for your department during an academic restructuring; to ensure growth and continued success.
Keywords: restructuring; advocacy; collaboration; faculty culture; chair leadership